Insurgent Encounters Transnational Activism, Ethnography, and the Political - Juris, Jeffrey S.; Khasnabish, Alex (Duke University Press, 2013)
Insurgent Encounters illuminates the dynamics of contemporary transnational social movements, including those advocating for women and indigenous groups, environmental justice, and alternative-cooperative rather than exploitative-forms of globalization. The contributors are politically engaged scholars working within the social movements they analyze. Their essays are both models of and arguments for activist ethnography. They demonstrate that such a methodology has the potential to reveal empirical issues and generate theoretical insights beyond the reach of traditional social-movement research methods. Activist ethnographers not only produce new understandings of contemporary forms of collective action, but also seek to contribute to struggles for social change. The editors suggest networks and spaces of encounter as the most useful conceptual rubrics for understanding shape-shifting social movements using digital and online technologies to produce innovative forms of political organization across local, regional, national, and transnational scales. A major rethinking of the practice and purpose of ethnography, Insurgent Encounters challenges dominant understandings of social transformation, political possibility, knowledge production, and the relation between intellectual labor and sociopolitical activism.Contributors. Giuseppe Caruso, Maribel Casas-Cortés, Janet Conway, Stéphane Couture, Vinci Daro, Manisha Desai, Sylvia Escárcega, David Hess, Jeffrey S. Juris, Alex Khasnabish, Lorenzo Mosca, Michal Osterweil, Geoffrey Pleyers, Dana E. Powell, Paul Routledge, M. K. Sterpka, Tish Stringer